2021
DOI: 10.33448/rsd-v10i11.19537
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da expansão urbana na Cidade de Maceió, Alagoas – Nordeste do Brasil

Abstract: O crescimento das cidades juntamente com a formação desordenada de grandes metrópoles ao redor do mundo resulta em grandes mudanças no uso e ocupação do solo. Porém, há poucos estudos que relacionem a expansão urbana e seus efeitos nas cidades do Nordeste do Brasil (NEB). Assim, o objetivo deste estudo foi avaliar a expansão urbana em Maceió-Alagoas entre 1985 e 2020 a partir de produtos orbitais Land Surface Temperature (LST) e Normalized Difference Vegetation Index (NDVI), com a finalidade de detectar as mud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Maceió is in ENEB between latitudes 9.40º to 9.70º S, and longitudes 35.80º to 35.60º W, with altitudes that vary between 0 and 100 m above mean sea level (NMM), located in the Atlantic Forest biome. (Santos, et al, 2022;Batista, et al, 2021), as shown in Figure 1. According to the Köppen-Geiger classification, it is categorized as tropical hot and humid 'As', with variations in temperature throughout the year.…”
Section: Study Areamentioning
confidence: 90%
See 2 more Smart Citations
“…Maceió is in ENEB between latitudes 9.40º to 9.70º S, and longitudes 35.80º to 35.60º W, with altitudes that vary between 0 and 100 m above mean sea level (NMM), located in the Atlantic Forest biome. (Santos, et al, 2022;Batista, et al, 2021), as shown in Figure 1. According to the Köppen-Geiger classification, it is categorized as tropical hot and humid 'As', with variations in temperature throughout the year.…”
Section: Study Areamentioning
confidence: 90%
“…The ARs with the highest positive asymmetric distributions were AR5 and AR6, populated neighborhoods with several changes in land use and occupation in recent decades (Correia-Filho, et al, 2019;Batista, et al, 2021). AR5 and AR6 move away from the symmetrical position along with AR8.…”
Section: Statistics Applied To Ndcmentioning
confidence: 98%
See 1 more Smart Citation
“…Essas condições térmicas também podem ser identificadas espacialmente por meio de técnicas de sensoriamento remoto, através da temperatura de superfície terrestre associada ao Normalized Difference Vegetation Index (NDVI) (Santos et al, 2016;Santiago, 2017;Prado & Silva, 2020). Essa associação possibilita a avaliação entre as modificações na ocupação do solo e a variação da temperatura local (Pereira dos Santos et al, 2020;Batista et al, 2021), visto que a substituição de áreas nativas em construções urbanas altera a temperatura local e interfere no conforto do ambiente para as pessoas residentes.…”
Section: Introductionunclassified